2019
DOI: 10.1186/s12891-019-2435-1
|View full text |Cite
|
Sign up to set email alerts
|

Does thread shape affect the fixation strength of the bioabsorbable interference screws for anterior cruciate ligament reconstructions? A biomechanical study

Abstract: BackgroundThe purpose of this study was to compare the biomechanical behaviour of two bioabsorbable interference screws with different geometries.MethodsTwo different pitch (2.5 and 5 mm) bioabsorbable interference screws, both 9 × 30 mm, were tested. Tests were performed with forty bovine digital extensor tendons and skeletally mature porcine tibiae. Two protocols of cyclic tests at 1 Hz were performed: 1000 cycles from 50 to 250 N, and 5000 cycles from 100 to 300 N (n = 10 for each type of test and screw). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the porcine knee anatomy is sufficiently similar to that of the human knee 38 and that porcine flexor tendons possess similar biomechanical properties to human hamstring tendons, 11 making the porcine knee model a setup used frequently to assess biomechanics of orthopaedic implants in knee surgery. 10 , 18 , 19 , 21 A graft diameter of 8 mm was chosen for this study, resembling the typical thickness of a hamstring ACL graft. Considering that some implants failed by damage to the implant-to-bone interface and that bone density in the porcine model is significantly higher in comparison with human specimens, 1 this may have biased the load to failure toward higher values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the porcine knee anatomy is sufficiently similar to that of the human knee 38 and that porcine flexor tendons possess similar biomechanical properties to human hamstring tendons, 11 making the porcine knee model a setup used frequently to assess biomechanics of orthopaedic implants in knee surgery. 10 , 18 , 19 , 21 A graft diameter of 8 mm was chosen for this study, resembling the typical thickness of a hamstring ACL graft. Considering that some implants failed by damage to the implant-to-bone interface and that bone density in the porcine model is significantly higher in comparison with human specimens, 1 this may have biased the load to failure toward higher values.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic loading was performed at a speed of 100 mm/s. Preconditioning was performed with 10 cycles at 250 N. Cyclic loading was performed with 1000 cycles between 0 and 250 N. 18 Subsequently, load to failure was applied at a speed of 25 mm/min. Elongation and load were recorded continuously during all tests.…”
Section: Methodsmentioning
confidence: 99%
“…This biomechanical study has several limitations to mention. Previous studies showed that the porcine knee anatomy and ligament biomechanics are adequately similar to humans, making it a frequently used model to assess biomechanical primary stability of orthopedic implants [ 10 , 12 , 17 , 31 ]. However, bone density in the porcine model is significantly higher in comparison to humans [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IFS utilized in this study have different geometries, most prominently different thread shapes and thread pitches, which could have possibly influenced the biomechanical properties of the screws. However, both geometries reflect implants currently available in clinical practice, and thread shape was shown not to influence biomechanical properties of interference screws [ 17 ]. The comparisons between the implants are limited to the timepoint zero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation